Burning stability of the coal-dust methane-air mixture in a recuperative burner; Journal of Physics: Conference Series; Vol. 894 : Modern problems of continuum mechanics and explosion physics - Moiseeva K. M. Kseniya Mikhaylovna (2017, 2017)
Title screen